Peran Pendidikan Islam dalam Menghadapi Tantangan Sekularisme - Sidiq, Hamid; Nurfitri, Tetin; Syahidin, Rif'at Ahmad (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
Islamic education in Indonesia today is faced with a challenge that seeks to separate religious affairs from worldly affairs, this ideology is secularism which seeks to spread an understanding among the world's younger generation. When this understanding has increasingly spread among the younger generation of Muslims, especially Islamic students in Indonesia, it is not impossible that the future values of Islamic teachings will lose their identity. To anticipate various bad possibilities among the younger generation of Indonesian Muslims, the role of Islamic education is very urgent to be implemented. This study used a qualitative research and the type of research used was library research. The data sources for this research are online scientific journals that discuss secularism. The data analysis technique in this study used the Miles and Huberman technique which was carried out in four stages, namely: reduction, presentation, and verification or validation. The results of this study indicate that Islamic education has a very urgent role to be implemented among the younger generation of Muslims in Indonesia. This role can be actualized through strong faith education, worship education, and moral education.